Design of Drone Fleet Management Model in a Production System of Customized Products - Cordova-Gonzalez, F; Olivares-Chiappa, V (Institute of Electrical and Electronics Engineers Inc., 2016)
In many manufacturing plants, there is a major problem in the internal logistics due to the high number of products, machines, and routes, especially in those manufacturing plants that produce low weight products. For example, many industries such as footwear, toys, plastic household goods and industrial products, among others, require assemblage products in small assembly lines, in small and customized lots according to customer requirements. In general, in this stage of the process, it is not available an efficient logistics system and an adequate level of automation in the transport of supplies, either for collecting materials or for distributing them. Transporting materials and semi-finished products into a plant using a fleet of drones, involves to take over the tasks associated to the size of the fleet of drones, routing decisions, and drone selection to perform a particular task. The aim of this paper is to propose a fleet managing model for VTOL-UAV drones (Vertical TakeOff and Landing - Unmanned Aerial Vehicle) that perform the delivery or pickup of supplies and materials in a production plant, also incorporating alternation in drone operations for an efficient use of energy in their batteries. When calculating the size of a fleet, the model determines that, in order to bear the peak demand of final products, it will be required a drone fleet of a certain amount of units (drones) depending on the load capacity, cycle time of the transport operation, and the demand of units to be manufactured. This amount of drones is able to meet the demand of products covering all the deviations in the parameters. Furthermore, it is incorporated the use of coefficients which involve deviations in the estimated demand, cycle time, load capacity and availability of the drone fleet. In this context, a computational tool has been developed in order to determine the amount of drones that comprise a fleet to perform certain logistical operations under diverse operating conditions, some of which can include the product demand for turn; volume, weight and shape of the products, power and speed of the drones, covered distance and finally warehouse and plant layout. A manufacturer of plastic is used as a reference model. In this situation, the final product, storage boxes for home of various sizes, are assembled by performing pickup of parts in warehouses and performing delivery to the assembly lines at the plant. This work is aimed to simulate and evaluate a model which represents the operation of a fleet of drones in the process of transporting materials. The model also includes the manufacture of semi-finished materials and parts in their respective workstations and final assembly of the products in their respective lines, incorporating the activity of replacing flat batteries for charged batteries. This model allows to evaluate the impact on production due to battery changes, especially the drones used for transport. © 2016 IEEE.